Stress redistributions in unit cells of fibre-reinforced polymer composites with interface degradation - Godoy, Luis Augusto (2013)
Experimental evidence indicates that the main damage mechanisms found in fibre-reinforced composites under static loading or environmental action are matrix damage, fibre damage and interface damage, leading to various forms of strong inhomogeneities at the micromechanical level. The main objective of this paper is to identify the stress redistributions that take place at the unit cell level, in which damage has already occurred due to an independent process. A deterministic approach is carried out to illustrate the main features of the transverse behaviour of a unidirectional fibre-reinforced composite under static loading. Damage is modelled by means of interface defects, in which the number and size of defects are considered as parameters of the damaged configuration and also by changes in material properties. The two-dimensional problem is solved using a general purpose finite-element code. The results show the extent of damage propagation to be expected in several configurations with inhomogeneities.